The Effect of Whey Protein Consumption on Postprandial Glucose, Insulin and Incretin Responses in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis of Acute-Term Controlled Clinical Trials - Zahra Salimi; Maryam Asadi; Anahita Mansoori (Journal of Nutrition and Food Security)
Background: Postprandial hyperglycemia is an important factor which contributes to glycemic status and complications of diabetes mellitus. This was a systematic review and meta-analysis that was conducted to evaluate the overall effect of whey protein consumption on postprandial glucose, insulin, and incretin hormone responses in patients with type 2 diabetes mellitus (T2DM). Methods: Web of Science, Cochrane Library, EMBASE, PubMed, and Scopus databases were searched to find acute-term controlled clinical trials investigating the effect of all types of whey proteins on products postprandial glucose (PPG) response as the main outcome and also insulin and incretin responses as secondary outcomes in patients with T2DM. Ten trials met the eligibility criteria. A random-effects model was used to obtain pooled effect size. Results: The pooled analysis of the included trials indicated a significant reduction in the mean of glucose in the area under the curve [standard mean difference (SMD)=-1.295, 95% CI: -1.878 to -0.712, P<0.001] and also an increase in the mean of insulin, gastric inhibitory polypeptide (GIP) and glucagon‐like peptide‐1 (SMD=0.562, 95% CI: 0.303 to 0.822, P<0.001, SMD=0.349, 95% CI: 0.074 to 0.624, P=0.013 and SMD=0.439, 95% CI: 0.154 to 0.724, P=0.003, respectively) in participants who consumed whey protein compared with the control group. Conclusion: According to the findings, whey protein intake is effective in reducing postprandial blood glucose as well as increasing postprandial insulin and incretin levels. Thus, whey protein can be considered a strategy to improve glycemic control in patients with T2DM.